Pelatihan Aktivasi Otak Kiri dan Otak Kanan bagi Siswa Sekolah Dasar - Linda Fitria; Refnadi Refnadi (Jurnal Aplikasi IPTEK Indonesia, 2017)
Education today is more oriented to the development of the left brain, characterized by the number of subjects and even additional lessons that focus more on improving intellectual intelligence. This makes the child more critical, likes to imitate but lacks ideas, low emotional control, and other consequences. The training aims to help students train the left brain and right brain. Both left and right hemispheres are important. They complement each other. In this training, the participants who are elementary school students are given Lego games. The method used in this training activity is discussion and practice. Based on the evaluation, it is concluded that this training is useful to stimulate the left brain and right brain of children, characterized by participants who are more creative, imaginative, collaborative, and communicative.